Lightweight concrete green wall panels / Nik Arina Mohd Senin and Sallehan Ismail - Mohd Senin, Nik Arina; Ismail, Sallehan (2023)
Coarse aggregate is one of the materials used in the concrete mixture to produce a strong concrete structure. Nevertheless, the use of the material has resulted to environmental problems. Lightweight Concrete Green Wall Panels is a product that can address issues in the ceramic industry and help alleviate environmental concerns in forests due to excessive aggregate quarrying. This research aims to develop a Lightweight Concrete Green Wall Panels by using crushed clay pottery to reduce the amount of waste in Malaysia. Data were collected through document review, design thinking, experimental approach, and secondary data analysis. The data was analysed using graphical representations from Excel software and by calculating the mean, average, and standard deviation of the specimens. Four types of concrete were prepared to produce the suitable concrete mixture including normal, 10%, 20%, and 30% of recycled crushed clay as a substitute for the coarse aggregate to produce the lightweight concrete. Based on the result in terms of compressive strength, tensile strength, density, and water absorption tests, a replacement rate of 30% was selected to assemble the prototype of the Lightweight Concrete Green Wall Panels.